2022
DOI: 10.3390/economies10030060
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies and Tokens Lifetime Analysis from 2009 to 2021

Abstract: The success of Bitcoin has spurred emergence of countless alternative coins with some of them shutting down only few weeks after their inception, thus disappearing with millions of dollars collected from enthusiast investors through initial coin offering (ICO) process. This has led investors from the general population to the institutional ones, to become skeptical in venturing in the cryptocurrency market, adding to its highly volatile characteristic. It is then of vital interest to investigate the life span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This study has similarities with the research of Gatabazi et al (2022) which examined the crypto life cycle in the 2013-2017 and 2009-2013 periods, the results show that in the 2013-2017 period crypto has a high risk where many cryptos live and die in that period when compared to the 2009-2013 period. This study has similarities in the form of comparison of the effects of certain events in different periods.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study has similarities with the research of Gatabazi et al (2022) which examined the crypto life cycle in the 2013-2017 and 2009-2013 periods, the results show that in the 2013-2017 period crypto has a high risk where many cryptos live and die in that period when compared to the 2009-2013 period. This study has similarities in the form of comparison of the effects of certain events in different periods.…”
Section: Discussionsupporting
confidence: 76%
“…So, this result shows that investors need to be vigilant in choosing the type of crypto that is safe from the threat of death. Types of cryptocurrencies that were popular in the period of 2009-2017 according to Gatabazi et al (2022) namely Litecoin (2011), Peercoin (2012, Ripple (2012), Alphacoin (2013 and Aircoin (2014Aircoin ( -2016. In 2021, new types of crypto are starting to come in, such as Bogged Finance (2021) and Recharge Finance (2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant difference between tokens and cryptocurrency. According to Mougayar [45], while the issue and verification of token transactions can be centralized and decentralized, cryptocurrencies can only be decentralized; while the price of tokens can be influenced by a very wide list of factors in addition to supply and demand (issuance of additional tokens, binding to other assets), the price of cryptocurrencies is fully regulated by the market; and while tokens do not necessarily have to be launched on their own blockchain, cryptocurrencies always have their own blockchain [58].…”
Section: Tokens and Cryptocurrencymentioning
confidence: 99%
“…There are many factors that affect confidence in cryptocurrencies, such as the currency's circulation rate. According to Paul Gatabazi et al 's analysis of the life cycle of cryptocurrencies and tokens from 2009 to 2021, they found that the risk of collapse of cryptocurrencies under independent blockchain is relatively high [3]. Centralized policies have made transactions easier and faster for many cryptocurrency users, but the absence of such policies can also lead to misjudgments about cryptocurrency transactions and retention periods.…”
Section: Confidence Affects Pricesmentioning
confidence: 99%